Konsep Desain Pusat Kebudayaan Bugis di Gorontalo dengan Pendekatan Arsitektur Analogi Simbolik - A. Alifah Nurul Amaliah; Lydia Surijani Tatura; Dara Fitriani (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Gorontalo is one of the areas with the largest population of Bugis people, starting from the habits and customs of the Bugis tribe that are inherent in Gorontalo, to being well received by the surrounding community, the diversity of the Bugis tribe in Gorontalo also has a positive impact on the people of Gorontalo. This is the main factor in designing the Bugis Cultural Center in Gorontalo. As time goes by, the development of contemporary society, culture begins to be forgotten, even the culture itself is not known in depth by people. Especially for teenagers who have forgotten their own culture. Therefore, the problems mentioned above can be resolved by providing a forum that introduces Bugis tribal culture in this modern era, with facilities that provide special arts areas, both educational and commercial, special museum areas for periodic art performances and performing arts, both music and dance. Perancangan Pusat Kebudayaan Bugis ini akan mengusung tema Analogi Simbolik, yang bangunannya akan menganalogikan simbol-simbol khusus dari adat suku Bugis. The design of the Bugis Cultural Center will carry the theme of Symbolic Analogy, where the building will analogize special symbols from the Bugis tribe's customs.